Characteristics of Banana Peel and Orange Peel Biobriquettes as Alternative Energy - Aryati Muhaymin Marali; Yudi Kurniawan; Arwin Arwin; Herdian Dwimas; Yasmin Zulfati Yusrina (P3KM Politeknik Pertanian Negeri Samarinda, 2026)
Leftover banana peels and orange peels are organic waste that can be used as a raw material for alternative energy in the form of biobriquettes. The high consumption of bananas and oranges in Balikpapan City has led to an increase in the amount of fruit peel waste, necessitating efforts to utilize this waste in a more optimal and environmentally friendly manner. This study aims to analyze the characteristics of biobriquettes made from banana peels and orange peels based on their calorific value, water content, and ash content, in accordance with SNI No. 1/6235/2000 standards. The research method employed was an experimental approach, utilizing varying particle sizes of 60 and 80 mesh, varying amounts of tapioca starch adhesive of 5% and 10%, and varying molding pressures of 2 tons and 4 tons. The stages of briquette production include drying, carbonization, charcoal refining, filtering, mixing the adhesive, molding, and re-drying. The study results showed that the best variation was obtained in 80 mesh briquettes with 5% adhesive and 4 tons of pressure, resulting in a calorific value of 6188.7 Cal/g, a moisture content of 6.27%, and an ash content of 7.42%. These results indicate that finer particles and higher molding pressure can improve briquette quality, as they produce a denser and more homogeneous structure, resulting in a more efficient combustion process. Meanwhile, excessive use of adhesive results in increased moisture and ash content and reduces the briquette’s calorific value. The results indicate that banana and orange peel waste have promising potential to be developed as a sustainable and environmentally friendly alternative energy source.